Ensuring access to HPV vaccines through integrated services: a reproductive health perspective - Amy E Pollack; Miranda Balkin; Lindsay Edouard; Felicity Cutts; Nathalie Broutet (The World Health Organization, 2007)
In 2006, a quadrivalent human papillomavirus (HPV) vaccine was licensed, and another vaccine may be licensed soon. Little is known about the practical considerations involved in designing and implementing cervical cancer prevention programmes that include vaccination as a primary means of prevention. Although the vaccine may ultimately be indicated for both males and females, young girls, or girls and women aged 9-25 years, will be the initial candidates for the vaccine. This paper describes avenues for service delivery of HPV vaccines and critical information gaps that must be bridged in order to inform future sexual and reproductive health programming. It proposes the role that the sexual and reproductive health community, together with immunization and cancer control programmes, could have in supporting the introduction of HPV vaccines within the context of current health systems.